Perancangan produk aplikasi resep interaktif pembuatan kue tradisional untuk anak-anak - Setya Putri Erdiana; Octaviyanti Dwi Wahyurini (Institut Seni Indonesia Yogyakarta, 2018)
Cooking can be done by all people including by kids. Parents can start to teach and give a trust to their children when they are in the school-age. Also, it’s good to introduce children how to cook in the early age because cooking have many positive impacts for children. A kid who learns to cook will have healthier eating habit rather than other kids. To make them interest to learn to cook, its better if parents know what their kid wants about what kind of food they want to cook. Usually, kids feel interested to something they used to see everyday, in this case is traditional snacks. Besides, presenting traditional snack recipes as content, parents can teach them about the cultures of the origin of those snacks. Therefore, I as a designer will design an application for children with local culture as content, an interactive recipe application how to cook traditional snacks. After do many kinds of designing methods, from spreading questionnaires until observation to a sample of target audiences, hope the results can fit in the needs and solve the problems. Also this application can teach children how to cook their own food and make them proud of their own Indonesian local culture. Key words: application, traditional snack recipes, children